2009
DOI: 10.1111/j.1526-4637.2009.00596.x
|View full text |Cite
|
Sign up to set email alerts
|

Opioid Metabolism and Effects of Cytochrome P450

Abstract: years researchers have enhanced our understanding of the metabolism and risk of drug interactions of numerous medications utilized by patients with pain conditions. Pain patients often are prescribed multiple medications that can inhibit or induce specific cytochrome P450 (CYP450) enzymes. This review will focus on the effect of the CYP450 enzyme system metabolism on opioid agents codeine, fentanyl, hydrocodone, hydromorphone, methadone, morphine, oxycodone, and oxymorphone, as well as the potential effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
69
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(70 citation statements)
references
References 56 publications
1
69
0
Order By: Relevance
“…Its plasma concentration may therefore vary as a result of physiologically reduced CYP3A4 activity in the liver (liver disease and aging) or co-administration of drugs either inducing or inhibiting CYP3A4. 9,10) As outlined above, individual differences in the plasma concentrations of fentanyl is likely to occur when applied to the skin because of the dosage form and metabolic characteristics of the drug itself.…”
mentioning
confidence: 99%
“…Its plasma concentration may therefore vary as a result of physiologically reduced CYP3A4 activity in the liver (liver disease and aging) or co-administration of drugs either inducing or inhibiting CYP3A4. 9,10) As outlined above, individual differences in the plasma concentrations of fentanyl is likely to occur when applied to the skin because of the dosage form and metabolic characteristics of the drug itself.…”
mentioning
confidence: 99%
“…For example, the proportion of ultrarapid metabolisers is higher (up to 29%) in Middle Eastern and Northern African populations, and lower (0.5%) in Asians (Stamer & Stuber, 2007); the proportion of poor metabolisers is lower in Asians and African Americans (Holmquist, 2009).…”
Section: Codeinementioning
confidence: 99%
“…It is metabolised in the liver primarily to noroxycodone and oxymorphone, but these metabolites have clinically negligible analgesic effects (Lalovic et al, 2006;. Oxymorphone, the production of which relies on CYP2D6, is more potent than oxycodone, but plasma concentrations are low; noroxycodone, the major metabolite and the production of which relies on CYP3A4, is only weakly active (Coluzzi & Mattia, 2005;Lalovic et al, 2006;Holmquist, 2009). Unlike codeine, inhibition of CYP2D6 with quinine does not reduce the analgesic effect of oxycodone (Lalovic et al, 2006).…”
Section: Oxycodonementioning
confidence: 99%
See 1 more Smart Citation
“…6 Co-administration of CYP450 inducers or inhibitors may result in pDDIs and affect a patient's safety. Small clinical studies of oxycodone pDDIs have demonstrated pharmacokinetic changes and associated clinical manifestations.…”
mentioning
confidence: 99%